STUDI KASUS : ASUHAN KEBIDANAN KOMPREHENSIF PADA NY B UMUR 27 TAHUN DI PUSKESMAS KEJAJAR 1 WONOSOBO - Nining Nining; Indrawati Aris Tyarini; Fibrinika Tuta Setiani; Romdiyah Romdiyah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still relatively high in Indonesia. One of the government’s efforts to overcome this is through the Comprehensive Midwifery Care scheme, which includes integrated midwifery care services starting from Pregnancy, Maternity, Newborn, Postpartum, Neonatal, to Family Planning (KB) written using the SOAP method in descriptive and narrative form and carried out continuous assessment (Continuity of Care). The aim is to provide Comprehensive Midwifery Care which is carried out in a Continuity of Care manner. The subject of this Report is Mrs. B, 27 years old in the Kejajar 1 Health Center area, who was assessed from March 29 2022 to May 9 2022. From the results of the study on pregnancies which were carried out 3 times, it was found that Mrs. B has a high risk of Anemia. At Maternity Mother Care Mrs. B no complications. At the BBL care for the baby, Ny. B no complications. At the Postpartum Mother Care, 3 assessments were carried out and there were no complications. On Neonatal Care By. Mrs. B was done 3 times and there were no complications, and in Family Planning (KB) care there were no complications and the mother wanted to use hormonal contraception, namely injections. The conclusion in this study is that the practice is in accordance with the theory and there are no gaps. Suggestions from the studies that have been carried out are that midwifery services continue to be carried out to increase early detection and prevention of complications.